말기 신질환 환자에서 다발성 공장 게실 및 혈관 이형성증에 의한 대량출혈 - 이준현(Jun Hyun Lee); 김욱(Wook Kim); 김정수(Jung Soo Kim); 전해명(Hae Myung Jeon) (Annals of surgical treatment and research, 2002)
Small bowel diverticulum, although not common and usually asymptomatic, can give rise to unexpected problems such as malabsorption, perforation, obstruction and bleeding. Bleeding from a diverticulum is often sudden and massive, therefore requiring emergency operation. We report herein a case of a 75-year-old man who presented with massive bleeding from multiple jejunal diverticula. He had been diagnosed with hypertensive end stage renal disease and treated with hemodialysis since 14 years previously. He was admitted with both hematemesis and hematochezia, and treated conservatively at first. However, bleeding continued and the anemia did not improve despite blood transfusions. An gastroduodenofiberscope and selected angiography revealed no bleeding focus. An emergency laparotomy was performed and multiple jejunal diverticula, distributed from 15 to 60cm distal to the ligament of Treitz, were found. A segment of the jejunum containing all diverticula was resected and end to end anastomosis was performed. A histologic examination revealed some dilated blood vessels in the submucosa of the diverticulum, which was compatible with the findings of the angiodysplasia. Based on these findings, we suggest that angiodysplasia was the cause of bleeding from the jejunal diverticula in this case. (J Korean Surg Soc 2002;63:513-516) KCI Citation Count: 0